"Pitahaya: identification of important elements in producing a quality product that will achieve Malaysia's best" / Firdous Abu Bakar - Abu Bakar, Firdous (Faculty of Business and Management, 2007)
This project paper focuses on the study is focused on the Grading of Quality fruits (Pitahaya) that will achieve Malaysia's Best. The Malaysia's Best brand is designed to be an umbrella brand that facilitates the promotion of Malaysia's agriculture produce both on the domestic and international markets. It offers customer instant product recognition and identification of Malaysia's quality and safety of agricultural produce.